2009
DOI: 10.1111/j.1582-4934.2008.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

PDCD4 gene silencing in gliomas is associated with 5′CpG island methylation and unfavourable prognosis

Abstract: Programmed cell death 4 (PDCD4) is a newly described tumour suppressor that inhibits oncogenesis by suppressing gene transcription and translation. Loss of PDCD4 expression has been found in several types of human cancers including the most common cancer of the brain, the gliomas. However, the molecular mechanisms responsible for PDCD4 gene silencing in tumour cells remain unclear. Here we report the identification of 5′CpG island methylation as the predominant cause of PDCD4 mRNA silencing in gliomas. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 38 publications
2
67
0
Order By: Relevance
“…It was reported that the PDCD4 protein and mRNA levels were often not correlated in human tumors (16,42). The loss of PDCD4 expression was associated with methylation of PDCD4 5'CpG islands in gliomas (42). In contrast, we have observed that the mRNA levels in hepatoma tissues were not suppressed compared with the levels in normal tissues (Ozaki et al unpublished data), despite suppression of the protein levels (13).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It was reported that the PDCD4 protein and mRNA levels were often not correlated in human tumors (16,42). The loss of PDCD4 expression was associated with methylation of PDCD4 5'CpG islands in gliomas (42). In contrast, we have observed that the mRNA levels in hepatoma tissues were not suppressed compared with the levels in normal tissues (Ozaki et al unpublished data), despite suppression of the protein levels (13).…”
Section: Discussionmentioning
confidence: 50%
“…The degradation of the protein was stimulated through activation of the Akt-mTOR-S6K signaling pathway and the MAP kinase pathway (11,12,14). It was reported that the PDCD4 protein and mRNA levels were often not correlated in human tumors (16,42). The loss of PDCD4 expression was associated with methylation of PDCD4 5'CpG islands in gliomas (42).…”
Section: Discussionmentioning
confidence: 99%
“…Low PDCD4 expression levels correlate with poor outcomes in patients with glioblastoma multiforme (11). The frequent loss of PDCD4 in glioblastoma multiforme is partly due to epigenetic silencing secondary to 5' cytosine-phosphate-guanine island methylation (12), in addition to overexpression of microRNA (miRNA)-21, which targets PDCD4 mRNA for degradation (13). Although several studies have examined PDCD4 in glioma, the detailed molecular mechanisms underlying the role of PDCD4 in glioma remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies also demonstrated that PDCD4 had an important role in the development of ovarian cancer [3][4][5] and glioma. 6,7 Recent studies show that PDCD4 is also involved in various inflammatory diseases. It has been reported that PDCD4-deficient mice are resistant to streptozotocin-induced type II diabetes and experimental autoimmune encephalomyelitis, 8 and are also protected from the lethality of lipopolysaccharide (LPS).…”
mentioning
confidence: 99%